The relationship between nominal wage and price flexibility: New evidence - Diego Solórzano; Huw Dixon (Banco de México, 2020)
The frequencies at which prices and wages are adjusted, interpreted as price and wage flexibility, are key elements in workhorse models used for policy analysis. Yet, there is little evidence regarding the relationship between these two sources of nominal rigidities. Using two large and highly disaggregated price and wage microdata sets, this paper provides evidence that the industries changing more frequently wages reset prices more often. Once the frequency of wage adjustments is accounted for, the share of labor costs becomes less relevant in explaining the frequency of price changes, calling for a reinterpretation on previous findings that the labor share is a robust determinant of the frequency of price adjustments. The results in this study have implications for New Keynesian models' microfoundations, as their predictions have proven to be sensitive to the nominal rigidities assumptions.
Keywords: E31; J31; C26; 330; Nominal Stickiness; Micro Price Data; Micro Wage Data; Frequency of Adjustments